Hypervalent Iodine Mediated Ring-Opening 1,3-Difluorination of Benzylidenecyclopropanes - Huang, Long-Ling; Li, Jia-Yi; Sun, Qigang; Zhao, Gui-Yang; Wang, Honggen; Li, Qingjiang (Synthesis, 2024)
1,3-Difluorinated compounds are characterized by their unique conformation, influenced by 1,3-dipolar minimization effects. However, their synthetic methods are relatively limited. Here, a ring-opening 1,3-difluorination of benzylidenecyclopropanes (BCPs) using HF·Py, mediated by an electron-poor hypervalent iodine reagent, which is generated in situ by the oxidation of o-nitroiodobenzene with mCPBA is described. The protocol features mild reaction conditions, good functional group tolerance, and moderate to good yields. Additionally, the synthetic utility of this method is showcased by further transformations of the olefin group and allylic fluoride motif.
Keywords: benzylidenecyclopropane; 1,3-difluorination; hypervalent iodine; Olah’s reagent; ring-opening